ΤΟ ΞΕΝΟ ΛΕΞΙΛΟΓΙΟ ΣΤΙΣ ΕΛΛΗΝΙΚΕΣ ΠΗΓΕΣ ΤΗΣ ΒΕΝΕΤΟΚΡΑΤΙΑΣ ΓΛΩΣΣΑΡΙΟ ΜΕΤΑΓΛΩΤΤΙΣΜΕΝΩΝ ΙΤΑΛΙΚΩΝ ΟΡΩΝ ΠΟΥ ΠΕΡΙΕΧΟΝΤΑΙ ΣΕ ΔΗΜΟΣΙΕΥΜΕΝΕΣ ΝΟΤΑΡΙΑΚΕΣ ΠΡΑΞΕΙΣ ΤΩΝ ΙΟΝΙΩΝ ΝΗΣΙΩΝ - ΝΤΟΚΟΣ, ΚΩΝΣΤΑΝΤΙΝΟΣ; ΜΕΛΕΝΤΗ, ΜΑΡΙΑ (Eoa kai Esperia, 1997)
One of the difficulties that a schoral faces with the Greek sources is theunderstanding of the Italian words which, having been tranferred into Greek,are used in thore sources. To meet that difficulty, the author has compiled aglossary of words of Italian origin which are found in already published sources.This glossary of plainly a practical character could eventually be amplifiedwith new additions.